Empirical Wavelet Transform Based Method for Identification and Analysis of Sub-synchronous Oscillation Modes Using PMU Data - Philip, Joice G.; Jung, Jaesung; Onen, Ahmet (Journal of Modern Power Systems and Clean Energy, 2024)
This paper proposes an empirical wavelet transform (EWT) based method for identification and analysis of sub-synchronous oscillation (SSO) modes in the power system using phasor measurement unit (PMU) data. The phasors from PMUs are preprocessed to check for the presence of oscillations. If the presence is established, the signal is decomposed using EWT and the parameters of the mono-components are estimated through Yoshida algorithm. The superiority of the proposed method is tested using test signals with known parameters and simulated using actual SSO signals from the Hami Power Grid in Northwest China. Results show the effectiveness of the proposed EWT-Yoshida method in detecting the SSO and estimating its parameters.
Keywords: Empirical wavelet transform; Oscillation mode; Phasor measurement unit; Power; Prony-based method; Sub-syn-chronoi oscillation; Subsynchronous oscillations; Transform-based methods; Wavelets transform; Yoshidum algorithm; Empirical wavelet transform (EWT); phasor measurement unit (PMU); Prony-based method; sub-syn-chronous oscillation; variational mode decomposition; Yoshida algorithm